8 - Political Uncertainty and its Impact on Social Service Delivery in Uganda - khisa, Moses (Africa Development, 2021)
A growing body of scholarship has underscored the role of elite bargains and compromises in fostering or obstructing socio-economic transformation. This has been conceptualized in terms of political settlement – a combination of power and institutions that underpins an established socio-political order. The idea of political settlement, associated with the works of Douglas North (and his collaborators), and especially Mushtaq Khan, has gained currency as a key explanatory variable in accounting for the failure of African states to provide quality public goods and services. In the case of Uganda, some scholars have suggested that the country’s current political settlement has failed to provide the basis for achieving structural transformation. This article questions the conceptual validity of political settlement, suggesting instead that a shift of the conceptual aperture reveals deep political uncertainty in Uganda, a key reason why the government of President Museveni and the state apparatus it presides over cannot undertake fundamental transformation. The article argues that political uncertainty in Uganda is manifest in at least four contentious issues: the constitution, electoral disagreements, the ambiguous role of the military and the unsettled question of presidential succession. In an environment of uncertainty, systematic and long-term planning is subordinated to short-term and ad hoc manoeuvres, thus obstructing the building of a firm foundation for structural transformation.